(3GdOQ GdSfi aj efGbH GdTjN YHO GdZfis
(3ChdgG (B:s
(3MeOkG def HQgf HHGgQ bOQJg CeG HYO aEf ef Sff eSHZ Cf habfi deYQaI Gdehdi GdcGed GdUhai hSeYJ efg ai JaSjQ cdGe Gddg JYGdi hCMGOjK fHjg s
(3BNQgG (B:s
(3Ke jRL Hg ai GdeYGQL GdQHGfjI hGdCSQGQ GdEdgjI MJi jUjQ cGedkG ecedkG hCgdkG eDgdkG hgPG gh GdebUhO ef GdTjN GdcGed hGddg Gdehab GfJgi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs